Andean Decision 876 - Common country brand regime, a pioneering and avant-garde standard, which will have a multilateral impact - Suárez Mallqui, Lourdes Milagros (2024)
The country Brand is a sign that many countries have today, however, it does not have recognition and protection at the multilateral level from the existing rules of Industrial Property, given this need the block of countries that make up the Andean Community, after several years of negotiation, has managed to approve the Andean Decision 876 on the Common Country Brand Regime, without a doubt this is a pioneering an highly avant-garde standard, which will have a multilateral impact in the coming years.This article analyzes the existing problems for the protection of a country brand, evidencing the need to have a specific regulation that recognizes and protects this sign, it also analyzes and comments on the most relevant aspects of the regulation contained in Andean Decision 876 and finally, it indicates what is the pending task in this matter, detailing the most important advances that have been made to date for the recognition and protection of the country brand before the World Intellectual Property Organization (WIPO), the highest international authority on the matter.